**Who are the experts?**Our certified Educators are real professors, teachers, and also scholars who use their scholastic expertise to tackle your toughest questions. Educators go v a rigorous application process, and every answer they submit is the review by our in-house editorial team.

You are watching: Factor x 4 13x 2 36

The job is to:

Find the roots of x^4 – 13x^2 + 36 = 0

We have the right to make the equation look at friendlier by letting x^2=y.

Then the equation becomes:

y^2 - 13y + 36 = 0

keeping in mind to achieve the number 13 from addition of factors of 36,...

Start her **48-hour free trial** to unlock this answer and thousands more. Gain beer-selection.com ad-free and cancel anytime.

The task is to:

Find the roots of x^4 – 13x^2 + 36 = 0

We have the right to make the equation look friendlier by letting x^2=y.

Then the equation becomes:

y^2 - 13y + 36 = 0

Keeping in mental to acquire the number 13 from addition of determinants of 36, and knowing that 36 can be derived by multiply 9 and also 4, the administrate becomes:

(y-9)(y-4) = 0

Hence y=9 or 4.

That analyze to x^2=9 => x=+3 or -3

or x^2=4 => x=+2 or -2

Therefore, the roots of the equation are:

**x1 = -3**

**x2 = -2**

**x3 = 2**

**x4 = 3**

To evaluate the systems graphically, click the attach at the bottom of this answer

authorized by beer-selection.com Editorial Team

Tushar Chandra

Educator due to the fact that 2010

12,621 answers

| Certified education

web page Citation

Share link

We have actually to find the root of x^4 – 13x^2 + 36 = 0. Together we have actually x increased to the power 4, we room going to have actually 4 roots.

Now let us see the offered equation :

x^4 – 13x^2 + 36 = 0

we see that -13 deserve to be composed as -4 – 9 so that the sum is -13 and the product is 36

=> x^4 – 4x^2 – 9x^2 + 36 = 0

=> x^2 ( x^2 – 4) – 9( x^2 – 4) = 0

=> (x^2 – 4)(x^2 – 9) =0

Now x^2 – 4 and also x^2 – 9 have the right to be factorized making use of the relationship x^2 – y^2 = (x – y)*(x + y)

=> (x – 2)(x + 2)(x – 3)(x + 3) =0

So for (x – 2) = 0, we have x = 2

for (x + 2) = 0, we have x = -2

for (x – 3) = 0 we have x = 3

and because that (x + 3) =0, we have actually x = -3

**Therefore the root of x^4 – 13x^2 + 36 = 0 are x = 2, x = -2, x = 3 and also x = -3.See more: What Aisle Is Certo In At Walmart Is Certo? Where Do I Find Pectin In The Grocery Store**

authorized by beer-selection.com Editorial Team

### Ask a Question

ask a inquirySubmit inquiry

### Popular Questions

see all

## Related Questions

Browse allMath

recent answer post September 23, 2012 at 9:50:17 afternoon

use Cardano’s algebra method to uncover the root of `x^3+6x^2+9x+4=0`

1 education answer

Math

latest answer post November 19, 2010 at 7:50:26 afternoon

discover the roots of the equation x^2 + 11 x + 28 = 0

4 educator answers

Math

latest answer post August 21, 2012 in ~ 5:11:42 pm

resolve the equation x^4-13x^2+36 = 0

1 education answer

Math

latest answer post November 19, 2010 at 8:26:59 to be

If 3sec^2 x - 4 = 0 find x value

2 education answers

Math

latest answer post August 18, 2012 at 6:48:12 afternoon

factor: x^2 + 13x + 40

2 educator answers

beer-selection.com will assist you with any book or any kind of question. Our summaries and analyses room written through experts, and also your concerns are answered by genuine teachers. sign up with beer-selection.com

apply to be an educator

### Recommended

### More

©2021 beer-selection.com, Inc. All rights Reserved